Youth Entrepreneurship Among Higher Education Students – A Qualitative Research of Entrepreneurial Intention and Education - Mendonça, Pedro; Braga, Vítor; R. Ferreira, Marisa; Braga, Alexandra; Carvalho, Amélia (Naše gospodarstvo/Our economy, 2022)
The area of entrepreneurship education is developing rapidly, potentially conveying positive effects to business education, innovation and economies. Our paper seeks to analyse the entrepreneurial intention of a group of higher education students, and the data includes 29 interviews, administered to students of Portuguese higher education institutions. The results obtained allowed to confirm some of the aspects described in the literature, although a few divergences were also found. It was also possible to clarify some of the theories associated with barriers to entrepreneurship. The main limitations are related with the sample size, opening space for future research with larger samples. The most important implications relate to the identified need for very specific topics in entrepreneurship education. However, the key contribution of the paper also lies in its qualitative research approach.